Structural characteristics of barium titanate ceramic - Nur Liyana Amiar Rodin, 1988- author; Wan Nurulhuda Wan Shamsuri, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014